Beliefs and Practices of Academic Reading and Writing in Researchers in Training - Jésica Franco (Universidad ORT Uruguay, 2023)
This study aimed to examine and explain teachers' and students' reading and writing practices and beliefs in a master's program at a public university in Mexico. We conducted qualitative cross-sectional research. A self-administered questionnaire with open-ended questions was used in the initial stage to examine two distinct beliefs of reading and writing and identify key actors. Six interviews with teachers and students were carried out during the second stage. The study corroborates that the different beliefs are not mutually exclusive but can simultaneously exist in the same person, though they may be weighted differently. Those who firmly hold transmissive beliefs understand that reading and writing are processes to obtain (decode) and transmit (encode) information. In practice, these people emphasize the importance of identifying main ideas, summarizing texts, writing following a structure and taking up ideas from other authors. On the contrary, those who mostly hold transactional beliefs think that reading and writing are creative, dialogic and meaning-construction processes. Some of their reading and writing practices focus on aspects such as: defining a standpoint regarding the text, investigating the context of the author or reader, and defining reading or writing purposes. The research highlights the possibility of reconceptualizing reading and writing in the academic context, valuing their epistemic function and transforming the prevalent discourse that conceives them as technical and universal skills, which can be improved by correctly applying grammatical rules or following effective formulas.